HUBUNGAN HIGIENE PENJAMAH SANITASI MINUMAN DENGAN KEBERADAAN BAKTERI Escherichia coli PADA MINUMAN JUS BUAH DI DAERAH TEMBALANG - Dyah Puji Lestari; Nurjazuli Nurjazuli; Yusniar Hanani Danudianti (Jurnal Kesehatan Masyarakat (Undip), 2015)
Fruit juice is one of a beverages that is easily obtained and become favorite beverages among the students. The making and presentation of beverages with the presence of bacteria contamination in beverages may will be influence by hygiene factors are not qualified. The purpose of this study was to analyze the relation between hygiene sanitation beverage with the presence of bacteria Escherichia coli on fruit juice beverages in the Tembalang. This study used observational research  with a cross sectional design. Total samples as many as 25 trader jus, data collection techniques by the laboratory tests and surveys. Data were analyzed using Fisher exact test. The results of the 25 samples showed 13 (52%) fruit juice samples, 11 (44%) samples of boiled water and 14 (56%) samples of water wash containing the bacteria Escherichia coli. There is a relationship between the quality of boiled water with the presence of bacteria E.coli in fruits juice (p=0,001), there is a relationship between the quality of water wash to the presence of bacteria E.coli in fruits juice (p=0,005), there is no relationship between handler hygiene with the presence of  bacteria E.coli in fruits juice (p=0,848), there is no relationship water sanitation with the presence of bacteria E.coli in fruits juice (p=1,000), there is no relationship between  sanitary equipment with the presence of bacteria E.coli in fruits juice (p=0,561), there is no relationship between trash conditions with the presence of bacteria E.coli in fruits juice (p=0,543). From this study it could be concluded that  the quality of boiled water and washing water are risk factors Escherichia coli bacteria contamination on fruit juice in Tembalang area.